NATIONAL DEMOCRATIC PARTY OF GERMANY IN THE CONTEXT OF ELECTORAL PREFERENCES’ RADICALIZATION - Гримська, М. І. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The peculiarities of far right political parties in Germany after World War II are outlined. Main stages  of  their  evolution  are  identified  and  each  of  them  is  characterized  in  details.  The establishment  of  the  National  Democratic  Party  of  Germany  is  described,  its  place  in  the  party system is presented, and ideology and values are characterized.